LANGUAGE STYLE OF DIDEK TEXT IN THE ISLANDS OF SELAYAR, SOUTH SULAWESI PROVINCE - Dafirah, Dra; Weda Kusuma, I Nyoman; Suarka, I Nyoman; Pudentia, Dr (e-Journal of Linguistics; Vol. 9 Januari 2015 No. 1, 2015)
This article aims to describe the language aesthetic elements of didek . Didek is an oral tradition that is presented in the form of song of unrequited-reply. One of the peculiarities of this oral tradition is the emphasis on aesthetic elements or beauty. The speakers / singers are required to always use a beautiful language while singing. Berangkat dari pandangan Roman Jakobson penulis membahas unsur estetika yang ditemukan dalam teks didek . Artikel ini akan berfokus pada pembahasan tentang estetika bahasa dalam teks didek yang mencakup penggunaan gaya bahasa berupa: diksi dan majas. Departing from the view of Roman Jakobson this article is  focused on a discussion of the aesthetic language of the didek text including the use of language style: diction and figures of speech.
Keywords: Language Style, Didek